LOGISTICAL FACTORS INFLUENCING DISASTER RESPONSIVENESS OF HUMANITARIAN ORGANIZATIONS IN KENYA (CASE OF KENYA RED CROSS SOCIETY) - Mwangi, Philip Muchiri; Anaya, Dr.Senelwa (International Journal of Supply Chain Management, 2020)
Purpose: The purpose of this study was to explore the logistical factors that influence the responsiveness of humanitarian organizations in Kenya. The specific objective was to determine how infrastructure, funding, warehousing and coordination influenced the responsiveness of humanitarian organization in Kenya. Methodology: The researcher selected case study approach with a focus on Kenya Red Cross Society (KRCS). KRCS was selected because it is the largest humanitarian organization in Kenya and has presence across the country. The target population was 329 employees of the Kenya Red Cross Society based in Nairobi and who ware directly connected to logistics. Stratified random sampling technique was used to select a sample of 60 respondents. The study used descriptive research design and chose questionnaire as the tool for data collection. The study was based on a conceptual framework hence descriptive statistical data analysis was ideal. Collected data was analyzed using descriptive and inferential statistics. Results: The study found that KRCS depended on donor funding and delay in funding impacted on disaster responsiveness. Road infrastructure affected logistics but this was beyond the control of humanitarian organizations. Another key finding of this study demonstrated that many organizations in disaster area worked independently without coordinating with each. Owing to the fact that humanitarian organizations have no control on infrastructure the study recommended that these organizations invest in equipment that will help them perform even with poor road infrastructure. Concerning reliance on donor funding the study found that KRCS was investing in commercial ventures that would guarantee a steady revenue stream. The researcher contents with this thinking and encourages more such investment. Unique contribution to theory, practice and policy: The study recommends that there should be better coordination among the various stakeholders to improve humanitarian effort.